1975
DOI: 10.1038/bjc.1975.268
|View full text |Cite
|
Sign up to set email alerts
|

The effect of an hypoxic cell sensitizer on tumour growth delay and cell survival. Implications for cell survival in situ and in vitro

Abstract: Summary.-The effect of a single treatment with 30 mg dimethylnitrosamine (DMN) and 6 ,ug actinomycin D (ACT), given at different time intervals (ACT application to DMN, 2 h before, simultaneously, 5, 9 or 48 h later), was tested in female Sprague-Dawley rats in relation to renal carcinogenesis; additionally, the animals were fed either a normal or a protein deficient diet.The ACT treatment did not significantly modify either the kidney tumour incidence or the survival time in the different groups fed a normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1977
1977
1987
1987

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…4a shows that, when 1 mg/g of the electron-affinic radiosensitizer is given before irradiation, a large dosereduction factor or " sensitizer enhancement ratio " is obtained, between 2 0 and 2-4 over the dose range 18 to 25 Gy on the X-rays-only curve in air. This value is similar to other large values reported for several types of experimental tumour in mice using a variety of assay systems (Sheldon, Foster and Fowler, 1974;Denekamp and Harris, 1975;Brown, 1975;Begg, 1977;Sheldon and Hill, 1977;McNally, 1975;Stone and Withers, 1975;Rauth, Kaufman and Thomson, 1975;Bleehen, 1976;Denekamp and Stewart, personal communication). It differs however from the value of 1 0 reported by Hewitt for a cell-dilution experiment on this tumour, Squamous Carcinoma D, where two i.v.…”
Section: Proportion Of Hypoxic Cellssupporting
confidence: 88%
“…4a shows that, when 1 mg/g of the electron-affinic radiosensitizer is given before irradiation, a large dosereduction factor or " sensitizer enhancement ratio " is obtained, between 2 0 and 2-4 over the dose range 18 to 25 Gy on the X-rays-only curve in air. This value is similar to other large values reported for several types of experimental tumour in mice using a variety of assay systems (Sheldon, Foster and Fowler, 1974;Denekamp and Harris, 1975;Brown, 1975;Begg, 1977;Sheldon and Hill, 1977;McNally, 1975;Stone and Withers, 1975;Rauth, Kaufman and Thomson, 1975;Bleehen, 1976;Denekamp and Stewart, personal communication). It differs however from the value of 1 0 reported by Hewitt for a cell-dilution experiment on this tumour, Squamous Carcinoma D, where two i.v.…”
Section: Proportion Of Hypoxic Cellssupporting
confidence: 88%
“…The repopulation studies reported here were found to confirm that cellular repopulation is more rapid after treatment with CCNU than after CY. The results presented here emphasize the complexity of the relationship between tumour-cell kill and growth delay (see also McNally, 1973McNally, ,1975aMcNally, , 1975bTwentyman, 1977). It would appear that the estimation of cell kill from tumour-growth delay data might be very difficult, although this has been attempted by Lloyd (1975) and by Griswold (1975).…”
Section: Discussionmentioning
confidence: 88%